Integration model of collaborative supply chain (2015)
The strategic members of collaborative supply chain have been looking for actions to synchronize their links. The purpose is to improve the customer service and fulfill the challenges of the globalized competitiveness. This trend is known as integrated supply chain and improves the companies performance as a whole. In this paper, an integration model of collaborative supply chain was developed considering the strategical, tactical and operational perspectives. To implement it, a measurement instrument was designed and validated statistically. Also a mathematical model using fuzzy logic was designed and applied among 36 small, medium and large Mexican companies to determine their integration level and propose specific actions that allow them to improve it.